Comparison of Positive Inotropic Agents in the Management of Acute Decompensated Heart Failure. Issue 5 (May 2020) - Kelly, Julie; Cheng, Judy; Malloy, Rhynn; Lupi, Kenneth
Abstract : Abstract: Current guidelines recommend the consideration of positive inotropes in patients with acute decompensated heart failure (ADHF) who have low cardiac index and evidence of systemic hypoperfusion or congestion. However, there is no evidence detailing the first line agent for the management of ADHF. The purpose of this study was to compare the safety and efficacy of dobutamine to milrinone for the treatment of ADHF. This was a single-center, retrospective study at a tertiary academic medical center, approved by Partner's Health Care Institutional Review Board. Patients included in this study were those admitted with ADHF who received dobutamine or milrinone from June 2015 to July 2017. A total of 95 dobutamine and 40 milrinone patients were included in the analysis. Median hospital length of stay was 12 days in the dobutamine group versus 10 days in the milrinone group ( P = 0.34). Rehospitalization within 30 days occurred in 29.5% of patients in the dobutamine group versus 17.5% of patients in the milrinone group ( P = 0.15). Median intensive care unit length of stay was 4.5 days in the dobutamine group versus 10 days in the milrinone group ( P < 0.01). All other minor end points including all-cause mortality, progression to renal failure within 72 hours, rehospitalization in 90 days, and urine output within 72 hours of therapy were not found to be statistically significant. In addition, a post hoc analysis compared major and minor outcomes between milrinone and dobutamine using linear and logistic regression with adjustment for baseline characteristics. There were not any statistically significant findings in the post hoc analysis. Overall, there were no statistically significant differences in outcomes between the 2 groups other than longer intensive care unit length of stay in the milrinone group.